Limitations of Electromyography in the Assessment of Abdominal Wall Muscle Contractility Following Botulinum Toxin A Injection - Tomazini Martins, Rodrigo; Elstner, Kristen E.; Skulina, Christian; Rodriguez-Acevedo, Omar; Read, John W.; Rowe, Dominic B.; Ibrahim, Nabeel (Frontiers in Surgery, 2019)
Purpose: Pre-operative botulinum toxin A (BTA) injection of the lateral obliques aims to facilitate the closure of large ventral hernia defects and decrease the risk of repair breakdown during the critical healing phase. The exact duration of post-operative BTA effect and top-up timing in cases at high risk of recurrence remains uncertain. This study was designed to assess the value of electromyography (EMG) in determining the appropriate time for BTA top-up. Methods: 56 patients underwent ventral hernia repair with pre-operative BTA infiltration of the lateral obliques. 11 patients at high risk of recurrence considered suitable for BTA top-up were assessed post-operatively with both functional computed tomography (CT) and EMG. CT assessed segmental contractility of each muscle layer. Single-point EMG assessed the activity of individual muscle layers bilaterally in the anterior axillary line. Results: CT showed (i) variable contractility of anterior and posterior muscle segments prior to BTA injection; (ii) absent or incomplete muscle paralysis in over half of all segments; (iii) increased BTA effect on progress scans; and (iv) non-uniform pattern of change in BTA effect between the anterior and posterior muscle. EMG demonstrated modest voluntary activity in most muscle layers. Compared to standard of reference (CT), EMG showed moderate sensitivity (0.62), poor specificity (0.48), poor accuracy (0.57) and incorrect grading in 71% of true positive results. Conclusions: As BTA effect wanes, single-point EMG cannot reliably determine functional muscle status. A novel finding is that BTA-induced paralysis of the abdominal muscles may be remarkably non-uniform in degree, distribution and duration.